Description of two new Geissleria species (Bacillariophyta) from Central and West tropical Africa - Cocquyt, Christine; Ndjombo, Edit Lokele (Phytotaxa, 2019)
During a recently started-up project in the Biosphere Reserve at Yangambi, DR Congo, an unknown Geissleria taxon was observed in a small tributary of the Congo River. This taxon is here described as new to science based on detailed light and scanning electron microscopy observations. Geissleria lubiluensis sp. nov. can be distinguished by the slightly tri-undulate valve margins and the very distinct annulus located at a distance of 3 striae from the apex. The comparison of this taxon with various other Geissleria taxa with resembling valve outline or with resembling annulus structure, led to the description of another new species: Geissleria fogedii sp. nov. reported by Foged from Ghana as Navicula paludosa. This taxon resembles very well Geissleria lubiluensis but differs in the distinct annulus located closer to the apex mostly at the distance of one stria, the broader valves and the denser striation.